Quantification of the Active Lateral Earth Pressure Changes on Retaining Walls at the Leading Edge of Steep Slopes - Wang, Kui; Liu, Gang; Zhang, Yuwei; Lin, Junzhi (Frontiers in Earth Science, 2022)
Retaining walls may become unstable when the steep slope angle of the top of the wall (β ) is greater than the internal friction angle of the earth behind the wall (φ). To examine this behaviour, an active earth pressure model test setup was designed with inclined backfill behind the wall, and corresponding finite element simulations were performed at the same dimensions. The active earth pressure variation patterns of the retaining wall under two displacement modes were studied: translation (T mode) and rotation around the bottom of the wall (RB mode). The experimental results corresponded well to the finite element simulation results. The study found that the experimental results coincided well with the results of the finite element simulation. The active earth pressure and the location of the resultant force points are both connected to the wall displacement pattern and slope angle.